2011
DOI: 10.1002/anie.201101757
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Control of Metal–Organic Framework Crystallization Investigated by Time‐Resolved In Situ X‐Ray Scattering

Abstract: MOFs scattering away: The mechanism behind the multistep synthesis of two metal–organic frameworks sharing the same metal and organic precursors was revealed by in situ time‐resolved small‐ and wide‐angle X‐ray scattering. Key factors governing the crystal assembly could be established (see picture: C gray, H white, N blue, O red, Al yellow, Cl green), including solvent, temperature, and precursor concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
153
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 186 publications
(165 citation statements)
references
References 51 publications
11
153
0
1
Order By: Relevance
“…Only a small number of mono technique ex-situ crystallization studies on the synthesis of different prototypical MOFs have been reported up to date; most notably studies using X-ray absorption [105], dynamic light scattering [106], atomic force spectroscopy [107] and X-ray diffraction [108]. Only a few in situ single technique diffraction studies under hydrothermal synthesis conditions have been published [109][110][111] until the first in situ multi-technique works on more complex MOF systems were reported [112,113]. These studies might open the door to a rational design of synthesis conditions targeting specific textural properties.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 98%
“…Only a small number of mono technique ex-situ crystallization studies on the synthesis of different prototypical MOFs have been reported up to date; most notably studies using X-ray absorption [105], dynamic light scattering [106], atomic force spectroscopy [107] and X-ray diffraction [108]. Only a few in situ single technique diffraction studies under hydrothermal synthesis conditions have been published [109][110][111] until the first in situ multi-technique works on more complex MOF systems were reported [112,113]. These studies might open the door to a rational design of synthesis conditions targeting specific textural properties.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 98%
“…For example, timeresolved in situ EDXRD studies of MIL-53(Fe) formation reveal the presence of the intermediated MOF-235 phase which eventually disappears on extended heating [60]. Stavitski et al [69] evaluated the crystallization pathway of NH 2 -MIL-101(Al) and NH 2 -MIL-53(Al) using in situ SAXS/WAXS, in which the appearance of the intermediate MOF-235(Al) was also observed. As evidenced, the transient intermediate 4-6 nm sized clusters of MOF-235(Al) serve as chemical reservoir for subsequent formation of the stable NH 2 -MIL-101(Al) and NH 2 -MIL-53(Al) phases.…”
Section: Introductionmentioning
confidence: 95%
“…The reason is that NH 2 ‐MIL‐101(Al) is transformed to NH 2 ‐MIL‐53(Al) during the loading process, when it is immersed in HCl aqueous solution for 10 h (Fig. (c)) …”
Section: Resultsmentioning
confidence: 99%